Factors Influencing Student Perceptions of Rhynchostylis Gigantea Illustrations and Stress Levels at Suan Sunandha Rajabhat University, Nakhon Pathom Campus - Pichaichanarong, Tawipas (IJCAS (International Journal of Creative and Arts Studies), 2025)
The main objectives of this study were to examine the situations, to analyze selected factors and to investigate the perceptions toward Rhynchostylis Gigantea Illustrations and Stress Levels of College of Communication Arts (CCA), Suan Sunandha Rajabhat University, Nakhon Pathom Campus. Data from 91 undergraduate students, questionnaires were analyzed. Understanding how visual representations influence psychological and emotional responses among students is a growing area of interest in educational research. In particular, the use of botanical illustrations in academic settings not only serves aesthetic and educational purposes but may also impact students' mental well-being. This study focuses on Rhynchostylis gigantea, a native orchid species of Thailand, and explores how illustrations of this flower are perceived by undergraduate students in terms of both visual appreciation and emotional impact at Suan Sunandha Rajabhat University, Nakhon Pathom Campus—specifically within College of Communication Arts (CCA)—student stress levels are a concern due to academic pressures and personal challenges. In this context, the integration of botanical illustrations into the learning environment raises important questions about their potential role in influencing student perceptions and reducing stress. The main objectives of this study were to examine the current situations related to student perceptions of Rhynchostylis gigantea illustrations, to analyze selected influencing factors such as academic standing and prior exposure to visual arts, and to investigate overall student perceptions and associated stress levels. Data were collected from 91 undergraduate students through structured questionnaires and analyzed to identify patterns and relationships between the illustrations and student well-being. Faktor-Faktor yang Memengaruhi Persepsi Mahasiswa terhadap Ilustrasi Rhynchostylis Gigantea dan Tingkat Stres di Universitas Rajabhat Suan Sunandha Kampus Nakhon Pathom Abstrak Tujuan utama dari penelitian ini adalah untuk memeriksa situasi, menganalisis faktor-faktor terpilih, dan menyelidiki persepsi terhadap Ilustrasi Rhynchostylis Gigantea dan Tingkat Stres di College of Communication Arts (CCA), Universitas Suan Sunandha Rajabhat, Kampus Nakhon Pathom. Data dari 91 kuesioner mahasiswa sarjana dianalisis. Memahami bagaimana representasi visual memengaruhi respons psikologis dan emosional di antara mahasiswa merupakan bidang minat yang berkembang dalam penelitian pendidikan. Secara khusus, penggunaan ilustrasi botani dalam lingkungan akademis tidak hanya melayani tujuan estetika dan pendidikan, tetapi juga dapat memengaruhi kesejahteraan mental mahasiswa. Studi ini berfokus pada Rhynchostylis gigantea, spesies anggrek asli Thailand, dan mengeksplorasi bagaimana ilustrasi bunga ini dipersepsikan oleh mahasiswa sarjana dalam hal apresiasi visual dan dampak emosional. di Universitas Suan Sunandha Rajabhat, Kampus Nakhon Pathom —khususnya di dalam Fakultas Seni Komunikasi (CCA)—tingkat stres mahasiswa menjadi perhatian karena tekanan akademis dan tantangan pribadi. Dalam konteks ini, integrasi ilustrasi botani ke dalam lingkungan belajar menimbulkan pertanyaan penting tentang peran potensialnya dalam memengaruhi persepsi mahasiswa dan mengurangi stres.Tujuan utama dari penelitian ini adalah untuk meneliti situasi terkini terkait persepsi mahasiswa terhadap ilustrasi Rhynchostylis gigantea, menganalisis faktor-faktor yang memengaruhi seperti status akademis dan paparan sebelumnya terhadap seni visual, dan menyelidiki persepsi mahasiswa secara keseluruhan dan tingkat stres terkait. Data dikumpulkan dari 91 mahasiswa sarjana melalui kuesioner terstruktur dan dianalisis untuk mengidentifikasi pola dan hubungan antara ilustrasi dan kesejahteraan mahasiswa.